The Interest UNICEF on Involvement of K-Pop Artists in Humanitarian Campaigns - Sabda Ningsih (JURNAL HAK : Kajian Ilmu Hukum, Administrasi Negara, dan Komunikasi, 2025)
This paper analyzes why UNICEF collaborates with K-Pop companies in conducting campaigns. Before the Korean Wave phenomenon hit the global stage, UNICEF had involved several non-state actors, the majority of whom were artists, as international or regional ambassadors. Only when K-pop has global fans is UNICEF interested in attracting several K-pop artists, such as BTS, Super Junior, and Everglow. This is one of the reasons UNICEF chose K-pop idols as ambassadors. Furthermore, K-pop fans have high loyalty and fanaticism toward their idols. They unconsciously make their idol's behavior, habits, and mindset an identity norm. They will also be aggressive towards outside groups who insult their idols. Seeing such characteristics benefits UNICEF because when K-pop artists become UNICEF ambassadors and spread human values, their fans will follow their idols and help the struggles of the K-pop artists they follow. Finally, there is a shared vision between K-pop idols and UNICEF. Having a shared vision will make it easier for both parties to plan actions and run campaigns.